Kekhasan Manhaj Tafsir Al-Mishbah Karya M. Quraish Shihab - Yusuf Budiana; Sayiid Nurlie Gandara (UIN Sunan Gunung Djati Bandung, 2021)
The Tafsir al-Mishbah can be said to be the greatest work of M. Quraish Shihab. The discussion of each chapter begins with an explanation of the main theme of the letter. Then the verses are grouped into certain sub-themes. The explanation of the verses is focused on explaining according to the theme and sub-theme. This makes it very easy for readers to be able to understand the meaning of the verses and letters being discussed. This paper is intended to analyze the interpretation method of al-Mishbah tafir, with more focus on his method. In general, the Al-Mishbah exegesis uses the tahlily method by interpreting the verses of the al-Qur'an from the various aspects contained in the interpreted verses and explaining the meanings contained therein. The interpretation of Al-Mishbah has two main features, namely social-culture (al-adabi al-ijtima'i) and the language aspect (lughowi). Al-Mishbah Tafsir is a bi al-ra'yi type of interpretation because its interpretation is more based on the results of ijtihad, whether ijtihad itself or by quoting the results of ijtihad by previous mufassirs. The presentation method adopted by Quraish Shihab makes it easy for the reader to understand the explanation presented. Based on the results of the study, it can be concluded that the interpretation of al-Mishbah has a special method that distinguishes it from interpretations that use other tahlily methods.